RELATIONSHIP BETWEEN WEIGHT STATUS AND BASAL METABOLISM IN SCHOOLCHILDREN: THE MODERATING ROLE OF DIET QUALITY AND PHYSICAL ACTIVITY (Kinesiology, 2023)
There is currently a scientific trend to study the association between energy balance and its impact on health from the earliest stages of life. The aim of this study was to examine whether diet quality and physical activity moderate the association between weight status and basal metabolism in a sample of Murcian primary schoolchildren aged 8-12 years. Basal metabolism was calculated according to height, sex, and weight, with fixed coefficients following validated formulae. Physical activity was measured with the Krece-Plus test; the KIDMED questionnaire was used to quantify diet quality and nutritional status was assessed by body mass index (BMI; kg/m2) adjusted for sex and age. The results obtained indicate that overweight schoolchildren had a higher basal metabolism than their normal-weight peers considering their diet quality and physical activity level (p